Differences in the Development of Adverse Infusion Reactions to Rituximab in Patients With Systemic Lupus Erythematosus, Rheumatoid Arthritis and Non-Hodgkin's Lymphoma-Enigma Variations - Gilaberte Reyzabal, Sergio; Isenberg, David (Frontiers in Medicine, 2022)
It has become clear that rituximab treatment is useful for both B-cell malignancies and autoimmune rheumatic diseases. However this treatment is associated with an increased risk of an allergic reaction. We have reviewed the frequency with which these reactions occur in these different conditions. They appear to be less frequent when rituximab is used to treat rheumatoid arthritis and systemic lupus perhaps because concomitant steroids are invariably given to these patients with the rituximab which is not necessarily the case with the treatment of B-cell malignancies.